Porous bioactive glass micro- And nanospheres with controlled morphology: Developments, properties and emerging biomedical applications - Zheng, Kai; Sui, Baiyan; Ilyas, Kanwal; Boccaccini, Aldo R. (Materials Horizons, 2021)
In recent years, porous bioactive glass micro/nanospheres (PBGSs) have emerged as attractive biomaterials in various biomedical applications where such engineered particles provide suitable functions, from tissue engineering to drug delivery. The design and synthesis of PBGSs with controllable particle size and pore structure are critical for such applications. PBGSs have been successfully synthesized using melt-quenching and sol-gel based methods. The morphology of PBGSs is controllable by tuning the processing parameters and precursor characteristics during the synthesis. In this comprehensive review on PBGSs, we first overview the synthesis approaches for PBGSs, including both melt-quenching and sol-gel based strategies. Sol-gel processing is the primary technology used to produce PBGSs, allowing for control over the chemical compositions and pore structure of particles. Particularly, the influence of pore-forming templates on the morphology of PBGSs is highlighted. Recent progress in the sol-gel synthesis of PBGSs with sophisticated pore structures (e.g., hollow mesoporous, dendritic fibrous mesoporous) is also covered. The challenges regarding the control of particle morphology, including the influence of metal ion precursors and pore expansion, are discussed in detail. We also highlight the recent achievements of PBGSs in a number of biomedical applications, including bone tissue regeneration, wound healing, therapeutic agent delivery, bioimaging, and cancer therapy. Finally, we conclude with our perspectives on the directions of future research based on identified challenges and potential new developments and applications of PBGSs.
CRIS-Team Scopus Importer:2021-03-05